A synthesis of scale-dependent ecology of the endangered mountain caribou in British Columbia, Canada - Serrouya, Robert; McLellan, Bruce N.; Apps, Clayton D.; Wittmer, Heiko U. (Rangifer, 2008)
Mountain caribou are an endangered ecotype of woodland caribou (Rangifer tarandus caribou) that live in highprecipitation, mountainous ecosystems of southeastern British Columbia and northern Idaho. The distribution and abundance of these caribou have declined dramatically from historical figures. Results from many studies have indicated that mountain caribou rely on old conifer forests for several life-history requirements including an abundance of their primary winter food, arboreal lichen, and a scarcity of other ungulates and their predators. These old forests often have high timber value, and understanding mountain caribou ecology at a variety of spatial scales is thus required to develop effective conservation strategies. Here we summarize results of studies conducted at three different spatial scales ranging from broad limiting factors at the population level to studies describing the selection of feeding sites within seasonal home ranges of individuals. The goal of this multi-scale review is to provide a more complete picture of caribou ecology and to determine possible shifts in limiting factors across scales. Our review produced two important results. First, mountain caribou select old forests and old trees at all spatial scales, signifying their importance for foraging opportunities as well as conditions required to avoid alternate ungulates and their predators. Second, relationships differ across scales. For example, landscapes dominated by roads and edges negatively affect caribou survival, but appear to attract caribou during certain times of the year. This juxtaposition of fine-scale behaviour with broad-scale vulnerability to predation could only be identified through integrated multi-scale analyses of resource selection. Consequently we suggest that effective management strategies for endangered species require an integrative approach across multiple spatial scales to avoid a focus that may be too narrow to maintain viable populations. Abstract in Norwegian / Sammendrag:Skala-avhengig økologi og truet fjellvillrein i Britisk ColumbiaFjellvillreinen i de nedbørsrike fjellområdene i sørøstre Britisk Columbia og nordlige Idaho som er en truet økotype av skogsreinen (Rangifer tarandus caribou), har blitt kraftig redusert både i utbredelse og antall. Mange studier har vist at denne økotypen er avhengig av vinterføden hengelav i gammel barskog hvor det også er få andre klovdyr og dermed få predatorer. Slik skog er også viktige hogstområder, og å forstå økologien til fjellvillreinen i forskjellige skaleringer er derfor nødvendig for å utvikle forvaltningsstrategier som kan berge og ta vare på denne reinen. Artikkelen gir en oversikt over slike arbeider: fra studier av begrensende faktorer på populasjonsnivå til studier av sesongmessige beiteplasser på individnivå. Hensikten er å få frem et mer helhetlig perspektiv på fjellvillreinen og finne hvordan de begrensende faktorene varierer etter skaleringen som er benyttet i studiet. Oversikten vår frembragte to viktige resultater; 1) Uansett skalering så velger dyrene gammel skog og gamle trær. 2) Dyrenes bruk av et område kan variere med benyttet skalering, for eksempel vil landskap utbygd med veier og hogstflater være ufordelaktig for overlevelsen, men synes likevel å kunne tiltrekke fjellvillreinen til visse tider av året. Forholdet mellom atferd ut fra fin-skalering og stor-skalering sårbarhet hva gjelder predasjon, ville kun blitt avdekket ved flere-skaleringsanalyse av hvordan ressursene benyttes. Ut fra dette foreslår vi at forvaltningsstrategier for truete bestander som eksempelvis fjellvillreinen, må baseres på tilnærminger ut fra ulike skaleringer for å hindre at et for snevert perspektiv kan begrense muligheten for vedvarende levedyktighet.